SCIENTIFIC AND INNOVATIVE ACTIVITIES OF NNGASU - Ilya S. Sobol; Andrey A. Lapshin; Dmitriy V. Monich (Высшее образование в России)
The article considers the main features of scientific and innovative activities of Nizhny Novgorod State University of Architecture and Civil Engineering. It views the fundamental and applied areas of research, R&D, highlights the activities of interbranch engineering centre, and introduces its basic qualitative results and achievements.